Pengaruh Daya Tarik Iklan, Kompetensi Tenaga Penjual, Persepsi Kualitas Layanan E-Banking Terhadap Minat Penggunaan Jasa Layanan E-Banking Bank BNI (Studi Kasus Pada Bni Kantor Layanan Unila) - Baity, Nur (Universitas Malahayati, 2019)
The purpose of this study was to determine the effect of attractiveness of advertisements, thecompetence of salespeople and perceived of e-banking service quality on interest use in Bank BNI ebanking.This research is a qualitative study with a survey technique involving 95 Savings Pluscustomers at the University Service Office. Data collection uses a questionare, which is then analysedusing multiple linier regression analysis. The result of the study: (1) The attractiveness ofadvertisements, the competence of salespeople, and e-banking service quality influence the interest usein Bank BNI e-banking services, amounting to 47,5%, each independent variable contribute 19,51%,14,61% and 13,38%.; (2) Partially the attractiveness of advertising has a positive effect about 16,5%,and the quality of Bank BNI e-banking services is 20,8%.Investment in technology not only providesefficient benefits and effectiveness but also is the added value that the company has to compete toobtain customers. This can be seen from the partial increase of three factors, namely theattractiveness pf advertisements, the competence of salespeople, and the quality of e-banking servicesthat can increase customer interest in using e-banking services.Keywords: e-banking services, attractiveness of advertising, competency of salespeople.